THE PRINCIPLES OF INDEPENDENT EVALUATION SYSTEM IN HIGHER EDUCATION - Nadezhda F. Efremova (Высшее образование в России)
The independent evaluation of the results of basic educational programs development becomes veryimportant in the conditions of transition of the national education system to competence training. The world’s best educational practices are based on the reliable evaluation systems. The development of such systems deserves special attention. This process in Russia runs very slow and difficult. The article dwells on the basic principles of constructing the quality assessment system in higher education points out the most common problems of formation of university funds assessment tools, pointed and suggests the most important ways to improve the actual situation.